Creative psychologists: reflections on teaching and pedagogic practice inspired by an arts-based Away Day - Paltoglou, Aspasia; Hopper, Jeremy (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
In an unusual departmental Away Day, instead of delving into discussions about established disciplinary modes of teaching and research, colleagues from the Department of Psychology at MMU were invited to attend a very different type of event, and to engage with explorative activities more associated with the creative arts. The idea behind the departmental event was to facilitate us to bond as a group but also to encourage us to pursue and develop continuing professional development (CPD) by engaging with elements of teaching and pedagogic practice from a very different disciplinary perspective. In this reflective commentary, the authors share their experience and reflections from taking part in and engaging with this meeting. The authors reflect on issues such as the effect of traditional academic criticism on students’ self-esteem and creativity, as well as alternative assessment and teaching methods that aim to enhance student agency and engagement. In summary, this Think Piece is a reflection on the authors’ creative selves, and the role of expressive freedom and creativity in relation to teaching psychology in higher education.